The scopes and possibilities of Slovakian pyrethrum production and marketing - Tóth, Štefan; Stričík, Michal; Týr, Štefan; Vereš, Tomáš (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2012)
This paper discusses the possibilities of pyrethrum Chrysanthemum cinerariaefolium (Trevir.) Vis. production in southern regions of Slovakia, with emphasis on target marketing, management constraints and further research. The pyrethrum is not a traditional crop in Slovakia, nowadays with perspectives on cultivation. The high yields and quality of some suitable pyrethrum ecotypes gives a ground of effective field production in favorable conditions. The pyrethrum production at yield 1.275 t of dried flowers per hectare at least 1.5 % of pyrethrum contain can be profitable, it could be the high lucrative crop with the economic result in the range 413 – 1071 € per ha. According to SWOT analysis it could be the final course the offensive strategy for the Slovakian pyrethrum production. The intensive production of this commodity needs further development. Prospects of this non-traditional crop in Slovakia are also promising in terms of development of farming systems on land, where the use of plant protection products of botanical origin is welcome. The possibilities of realization are more extensive by handling of the processing and stabilization of the extract.